PERBANDINGAN BOBOT HIDUP, KARKAS, GIBLET, DAN LEMAK ABDOMINAL AYAM JANTAN TIPE MEDIUM DENGAN STRAIN BERBEDA YANG DIBERI RANSUM KOMERSIAL BROILER - Dedi Setiadi; Khaira Nova; Syahrio Tantalo (JURNAL ILMIAH PETERNAKAN TERPADU, 2013)
Rooster medium type are constitute by-product of effort petelur's chicken hatch, one that is developed as breed of flesh producer. The success of the farm rooster medium type is influenced by many factors both external and internal factors. One of the internal factors which is also important in determining the growth rate is strain. The research aimed to determine the strain of roosters medium type which has better live weight, carcass, giblet, and abdominal fat by giving commercial broiler ration.  This research was up to 7 weeks of held from 19 May--7 July 2012 in the chicken coop of Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. The roosters used are roosters medium type strain Isa Brown and Lohman as many as 200 heads (with each strain 100 tails). This research consisted of two treatments, those are T1: Roosters medium type strain Isa Brown and T2: Roosters medium type strain Lohman. For each treatment consisted of 20 experimental plots with the trial unit for each plot is 5 heads. Of each that slot is taken 1 chicken to be made sample for pruned. The data obtained from this research was analyzed by using t-student test with significant level of 5% (Steel and Torrie, 1993). The variables observed were live weight, carcass, giblet and abdominal fat. The result of this research shows that: strain Isa Brown having living wight and karkas's wight the better than strain Lohman , although wight giblet and resulting abdominal fat both of strain that not different reality (P>0,05). Keywords: Roosters medium type, strain, live weight, carcass, giblet, abdominal fat